Prevalence of and risk factors for bacterial vaginosis among women of reproductive age attending cervical screening in southeastern Brazil - Marconi, Camila [UNESP]; Duarte, Marli T. C. [UNESP]; Silva, Daniela C.; Silva, Márcia G. [UNESP] (Elsevier B. V., 2015)
To determine the prevalence of and risk factors for bacterial vaginosis. A cross-sectional study of women aged 14-54 years attending 18 primary healthcare units in Botucatu, Brazil, for cervical screening was undertaken between September 1, 2012, and January 31, 2013. Data on sociodemographics, sexual behavior, and medical history were obtained by interview. Vaginal swabs were taken to classify the vaginal flora according to the Nugent scoring system. Candida sp. hyphae and infection by Trichomonas vaginalis were also evaluated by microscopy and culture, respectively. Stepwise logistic regression analysis was performed to identify risk factors independently associated with bacterial vaginosis. Among 1519 women included in analyses, 457 (30.1%) had bacterial vaginosis. Variables independently associated with bacterial vaginosis were a single marital status (OR 1.4; 95%CI 1.1-1.8), partner infidelity (OR 1.5; 95%CI 1.2-1.9), abnormal discharge in the previous year (OR 1.5; 95%CI 1.2-2.0), and concurrent trichomoniasis (OR 4.1; 95%CI 1.5-11.5). Current use of hormonal contraception (OR 0.7; 95%CI 0.5-0.9), luteal phase of menstrual cycle (OR 0.8; 95%CI 0.6-0.9), higher income (OR 0.8; 95%CI 0.6-0.9), and vaginal candidiasis (OR 0.5; 95%CI 0.3-0.9) all had protective effects. The prevalence of bacterial vaginosis in the study population is high. The epidemiological data provide evidence of the sexual transmissibility of bacterial vaginosis.
Keywords: Bacterial vaginosis; Risk factor; Sexual behavior; Sexually transmitted infection